Mediation in civil and commercial matters in Spain: From voluntary to mandatory - Feliu Rey, Jorge (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
Given the still limited use of mediation in civil and commercial matters in Spain, various measures have been taken to overcome the various obstacles to its implementation. The legislative transition from a voluntary model to a mandatory one based on a formula of the requirement of procedure is to be understood within such a strategy. In this article, this evolution is analyzed and its effects are assessed. In addition to the legislator, the parties, by agreement, also promote the use of mediation inn their contracts, by agreeing on its use prior to arbitration, or through hybrid clauses.
Keywords: Mediation; arbitration; voluntary; mandatory; requirement of procedure; ADR